The influence of biocarrier of Aspergillus niger and Trichoderma harzianum toward vegetative growth of sorghum in the field experiment - Arwan Sugiharto; Toga Pangihotan Napitupulu; I Made Sudiana (Journal of Microbial Systematics and Biotechnology, 2020)
Compared to other cereal crops, sorghum has a higher drought tolerance trait. However, efforts are needed to increase the productivity of sorghum, particularly in drought marginal land. One strategy to be implemented is the utilization of soil microorganisms formulated with biocarrier. Therefore, the aim of this study was to evaluate the influence of the fungal strain Aspergillus niger and Trichoderma harzianum formulated with compost and zeolite as biocarrier towards vegetative growth of sorghum. The field experiment was designed as a randomized block designed, factorial pattern with 4 replications. The first factor was selecting biocarrier, namely zeolite, compost, and a mixture of zeolite: compost (1:1). The second factor was the fungal inoculants, A. niger, and T. harzianum. The observed parameter was the growth profile of sorghum during vegetative growth, including stalk diameter and height. The results showed that the type of biocarrier, as well as the fungal strains did influence the growth of sorghum. The highest stalk diameter and height of sorghum were obtained after application of A. niger formulated with a mixture of zeolite: compost (1:1), with 17% and 41.2% higher than control, respectively. This condition shows that a mixture of zeolite and compost is seemingly able to create better micro-ecological conditions for fungal microbes to function effectively. Therefore, our findings suggested the addition of zeolite to compost for the application of biocarrier in the field experiment.